DARI TEORI KE PRAKTEK: PERSEPSI MAHASISWA PPG TERHADAP KETERPADUAN MATERI PPA 2 DAN PPL 2 - Mira Amazila, Rezi Anggraini, Beniario, Wahyuningsih Luth Neli Samira, Sri Suriyani (Inovasi Pendidikan, 2025)
This study explores the perceptions of English Teacher Professional Education (PPG) students toward the integration of the Principles of Teaching and Assessment (PPA 2) course with Field Teaching Practice (PPL 2). Utilizing a descriptive quantitative approach, data were collected through a Likert-scale questionnaire distributed to 30 students who had completed both courses during the 2024/2025 academic year at Universitas Muhammadiyah Sumatera Barat. The instrument included four indicators: understanding of PPA content, relevance of PPA and PPL materials, and overall integration between the two. The findings reveal overwhelmingly positive student perceptions. Specifically, the average scores for each indicator were consistently in the high range (Likert scale 4–5): understanding of PPA content (M = 47.59), relevance of PPA to guided teaching practice (M = 47.42), relevance of PPA to independent practice (M = 46.78), and overall integration between PPA and PPL (M = 49.46). More than 67% of respondents selected “strongly agree” for key items, indicating that students perceived the theoretical concepts in PPA as highly applicable in real classroom practice. These results affirm that the integration of PPA 2 and PPL 2 contributes significantly to developing pedagogical, professional, and reflective competencies among pre-service teachers. The study recommends continued alignment between theoretical coursework and practicum experiences to enhance teacher readiness and instructional effectiveness.